LAHIR DI LUAR PERKAWINAN PASCA PUTUSAN MAHKAMAH KONSTITUSI (Suatu Kajian dalam Perspektif Hukum Islam) - Yusnardi, Syahrizal Abbas, Adwani (Jurnal Ilmu Hukum, 2013)
Abstract:this research looks at the Islamic guardianship (wali) system of marriage for illegitimate female children post constitutional court decisionNo. 46/PUU-VIII/2010 in the perspective of islamic law. One of the purposes of the decree is to provide the fulfillment of children's rights and biological father’s responsibilities, especially in civil rights. However, if there is no limitation in interpreting civil relations between biological father and illegitimate child, the Constitutional Court's decree may lead to some concerns of various parties, especially Muslims in Indonesia. For example, the establishment of lineage relationships (nasab) of illegitimate child to the biological father and the permissibility of marriage guardianship (wali) to biological father of extramarital daughter, whether the child conceived in a valid marriage conducted according to Islamic law but not registered in State law or as a result of adultery. The method used in this study is a normative juridical method of descriptive analytical research. The purpose of this research is to know and to examine the Constitutional Court's decision in the perspective of Islamic law, especially regarding: 1) the lineage relationship with the biological father of an illegitimate child 2) the biological father marriage guardianship of an illegitimate daughter and, 3) the judicial consequences of biological father as a marriage guardian to a daughter born out of wedlock according to Islamic law. Keywords : The Islamic guardianship system of marriage,illegitimate children, biological father, the lineage relationship, constitutional court decision, the judicial consequences. Abstrak: Penelitian ini mengkaji mengenai hak perwalian nikah anak perempuan yang lahir di luar perkawinan pasca Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010 dalam perspektif hukum Islam. Salah satu tujuan dari putusan tersebut adalah untuk memberikan pemenuhan hak anak dan pertanggung jawaban dari ayah biologis, khususnya dalam hal hak keperdataan. Namun, apabila tidak adanya batasan dalam menafsirkan hubungan perdata antara ayah biologis dengan anak di luar perkawinan, putusan MK tersebut dapat menimbulkan kekhawatiran berbagai pihak, khususnya umat Islam di Indonesia, antara lain dapat ditetapkannya hubungan nasab anak di luar perkawinan kepada ayah biologisnya dan diperbolehkannya hak perwalian nikah ayah biologis terhadap anak perempuan hasil di luar perkawinan, baik dalam makna luar perkawinan sebagai perkawinan yang dilaksanakan sesuai agama namun tidak dicatatkan, maupun dalam makna luar perkawinan sebagai akibat/ hasil dari perzinaan.Metode penelitian yang digunakan adalah metode penelitian yuridis normatif, dengan spesifikasi penelitian deskriptif analitis.Adapun tujuan penelitian ini yaitu mengetahui dan mengkaji Putusan MK menurut perspektif hukum Islam khususnya mengenai : 1) hubungan nasab ayah biologis dengan anak yang lahir di luar perkawinan, 2) hak perwalian nikah ayah biologis terhadap anak perempuan yang lahir di luar perkawinan. Dan, 3) mengkaji konsekuensi yuridis hak perwalian nikah ayah biologis bagi anak perempuan yang lahir di luar perkawinan menurut hukum Islam. Kata kunci : Perwalian nikah, anak luar perkawinan, ayah biologis, hubungan nasab, putusan mahkamah konstitusi, konsekuensi yuridis